A PID Control System for Lower-Limb Rehabilitation Robot with a Function for Pedal Torque Estimation - Jing, Yue; Wang, Zewen; Wu, Qiwei; She, Jinhua; Kawata, Seiichi (Journal of advanced computational intelligence and intelligent informatics, 2025)
This article presents a proportional integral derivative (PID) control system for lower-limb rehabilitation robot that not only features satisfactory control performance for the pedal angle but also provides a function for pedal torque estimation. Nonlinear state feedback simplifies the stability analysis and control system design. The stability condition of the closed-loop system is derived based on a Lyapunov function. The PID controller ensures that the pedal angle tracks the reference trajectory. The equivalent input disturbance (EID) method in the control system was compared with the disturbance observer (DOB) and extended state observer (ESO) methods in terms of pedal torque estimation performance. The simulation results indicated that the EID method achieved a root mean square error of 0.37 N·m with 47.6% and 51.8% improvements over the DOB and ESO methods.